Antibiotic-Resistant Escherichia coli in Women with Acute Cystitis in Canada - Warren J McIsaac; Rahim Moineddin; Christopher Meaney; Tony Mazzulli (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Trimethoprim-sulfamethoxazole (TMP-SMX) has been a traditional first-line antibiotic treatment for acute cystitis; however, guidelines do not recommend TMP-SMX in regions where Escherichia coli resistance exceeds 20%. While resistance is increasing, there are no recent Canadian estimates from a primary care setting to guide prescribing decisions.